Determinant of Household Food Consumption Diversity in Lampung Province - Wuryaningsih Dwi Sayekti; Dyah Aring Hepiana Lestari; Desmarita Nugrahanti (Jurnal Ilmu Pertanian Indonesia, 2026)
Changing more diverse food patterns and reducing rice consumption were efforts to improve food quality to get superior human resources. The goal of this study was to detect household food consumption diversity in Lampung Province using the Berry Index (BI) and to investigate its determinants. This study utilized secondary data from the 2019 National Social Economic Survey (NSES). The sample size for this study was 9,046 households. The BI technique was utilized to examine household diversity, while linear multiple regression was employed to identify the factors influencing food consumption diversification. The findings revealed that most families were classified as moderately diverse, with an average BI of 0.826. Household food diversity was determined by household income, number of household members, age of head of family, education of head of household and housewife, type of area, gender of household head, and level of welfare. Keywords: Berry Index, diversification, food share, Lampung Province